Unusual epimerization in styryllactones: synthesis of (-)-5-hydroxygoniothalamin, (-)-5-acetylgoniothalamin, and O-TBS-goniopypyrone - Kotammagari, Tharun K.; Paul, Sayantan; Bhattacharya, Asish K. (ACS Omega, 2019)
(-)-5-Hydroxygoniothalamin, (-)-5-acetylgoniothalamin, and (+)-5-hydroxygoniothalamin, isolated from the Goniothalamus genus, are synthesized from triacetyl-O-D-glucal by employing the Ferrier reaction, Mitsunobu reaction, and Jones oxidation as key steps. The synthetic procedure also yields the epimers of (-)-5-hydroxygoniothalamin and (+)-5-hydroxygoniothalamin employing acid-mediated transition-metal-free epimerization at C-5 of styryllactones. Further studies reveal that the epimerization is facilitated by the phenyl group present on the styryllactones. Also, depending on the dihydroxylation reaction conditions, various analogues of saturated styryllactones are synthesized utilizing oxa-Michael reaction conditions.

Unveiling the cell wall-targeting mechanisms and multifaceted virulence modulation by a eugenol glycoconjugate against aspergillus fumigatus: insights from in vitro and in ovo studies - Gupta, Lovely; Verma, Shalini; Goswami, Lakshmi; Kamboj, Himanshu; Sen, Pooja; Bhattacharya, Asish K.; Vijayaraghavan, Pooja (Journal of Applied Macrobiology, 2024)
Aim The primary objective of this study was to elucidate the putative cell wall-associated targets of compound 6i, a glycoconjugate of eugenol, in Aspergillus fumigatus, while also evaluating its toxicity and assessing histopathologic alterations in the liver, heart, and kidney of compound 6i-treated embryos using an in ovo model.Method To achieve this aim, compound 6i was synthesized, and a series of biochemical assays were performed to determine its impact on the fungal cell wall. Additionally, quantitative real time-PCR and liquid chromatography-mass spectrometry/mass spectrometry analyses were conducted to investigate changes in gene and protein expression profiles associated with melanin biosynthesis, conidiation, siderophore production, transcriptional regulation of beta-glucan biosynthesis, and calcineurin activity in A. fumigatus.Results The experimental findings revealed that compound 6i exhibited notable antifungal activity against A. fumigatus by perturbing cell wall integrity, hindering ergosterol, glucan, and chitin biosynthesis, and inhibiting catalase production. Moreover, relative gene expression and proteomic analyses demonstrated that compound 6i exerted both downregulatory and upregulatory effects on several crucial genes and proteins involved in the aforementioned fungal processes. Furthermore, increased expression of oxidative stress-related proteins was observed in the presence of compound 6i. Notably, the glycoconjugate of eugenol did not elicit cytotoxicity in the liver, heart, and kidney of chick embryos.Conclusion The current investigation elucidated the multifaceted mechanisms by which compound 6i exerts its antifungal effects against A. fumigatus, primarily through targeting cell wall components and signaling pathways. These findings underscore the potential of the eugenol glycoconjugate as a promising antifungal candidate, warranting further exploration and development for combating A. fumigatus infections.
Keywords: Aspergillus fumigatus; cell wall integrity; Eugenol; Glycoconjugate; Transcription regulators; Virulence